Pembuatan dan Pengujian Troli Lipat (Studi Kasus di Toko atau Mall) - Wijaya Kelana Nur Soleh; Prantasi Harmi Tjahjanti (Jurnal Abdimas ADPI Sains dan Teknologi, 2023)
Until now, manual trolleys that are used for goods or as a tool to help move goods from one place to another still use human power, The difference in the design of the trolley that I made and the trolley that is usually used at my research site is that the trolley can be folded which has the advantage of being a place to put the trolley and easy to carry the trolley either in two-wheeled vehicles or in four-wheeled vehicles. This research is based on ideas from the results of research in work areas such as malls, and minimarkets. The folding trolley that is being made at this time can withstand a compressive load test of up to 875kg with one damaged component, namely a broken wheel, while in a medium compressive load test of 245kg with a safe wheel condition there is no damage to the component but the occurrence of curvature on the middle of the trolley, the folding trolley which previously had a height from the tile to the bottom limit of the trolley which was 9cm and when given a moderate compressive load test of 245kg there was a bend of 0.3cm which means the current trolley height is 8.7cm and a low compressive load test was carried out with a loading press 35kg to 105kg the folding trolley does not change in height, which means the trolley is still 9cm. The final results show that this folding trolley can be used in the field.